HASIL PRODUK SEMIOTIKA - Isman, Raya Nazwa; Badriyah, Siti (Institut Seni Indonesia Surakarta, 2022)
The purpose of semiotic analysis is to find the meaning of signs, including the things that are hidden behind a sign. Semiotics (semiotics) is a theory about the giving of 'signs'. In general, semiotics is classified into three basic concepts. The interior design of this room displays a concept that meets the criteria for sufficient space in lighting. This room is designed to be as comfortable as possible with very sufficient lighting. It's the same as the semiotics of light that marks this room